A novel cyano functionalized silica-titania oxide sol–gel based ionic liquid for the extraction of hazardous chlorophenols from aqueous environments. Issue 55 (18th May 2016) - Bakhshaei, Shabnam; Kamboh, Muhammad Afzal; Mohamad, Sharifah; Md Zain, Sharifuddin; Ma'amor, Azman
Abstract : The extraction of chlorophenols onSi-Ti@CN/IL is highly pH dependent and significant percent extraction was achieved at pH = 2. Abstract : In the present investigation a cyano functionalized silica-titania oxide sol–gel based ionic liquid (Si-Ti@CN/IL ) has been successfully synthesised via sol–gel immobilization of cyanopropyltriethoxysilane and 1-benzyl-3-(trimethoxysilylpropyl)imidazolium chloride ionic liquid (BTMP-IM ) on the silica-titania mixed oxide surface. The newly preparedSi-Ti@CN/IL was used as an adsorbent for the separation/preconcentration of chlorophenols from water samples prior to their HPLC-UV determination. Synthesis ofSi-Ti@CN/IL was confirmed by Fourier transform infrared (FT-IR) spectroscopy, field emission scanning electron microscopy (FESEM), Brunauer–Emmett–Teller (BET), thermo gravimetric analysis (TGA), X-ray diffraction (XRD) and elemental (CHNS) analysis. During the extraction process, various kinds of interactions such as π–π interactions and hydrogen bonding between the anionic/cationic sites were monitored. The extraction of chlorophenols onSi-Ti@CN/IL is highly pH dependent and a significant percent extraction was achieved at pH = 2. TheSi-Ti@CN/IL provided low limit of detection (LOD = 0.83–0.95 μg L −1 ) with a linearity range from 10–1000 μg L −1 (LOQ = 2.77–3.17 μg L −1 ). The field studies with high recovery (73.39–105.54%) as well as acceptable precision (%RSD 0.82–4.19) also supported the effectiveness ofSi-Ti@CN/IL, which could be useful for the extraction of selected chlorophenols from tap water, lake water and leachate from landfill sites. The comparative data supportSi-Ti@CN/IL as an effective extractant for selected chlorophenols.